Neutral phosphine phenol nickel catalyst with tert-butyl structure and preparation method of neutral phosphine phenol nickel catalyst

By introducing a tert-butyl structure into a nickel-based catalyst, the thermal stability and catalytic activity of the catalyst were improved, enabling efficient copolymerization of olefins and polar monomers. This resulted in the preparation of functional and high-performance polar polyolefins, solving the problems of insufficient thermal stability and activity in existing technologies.

CN121471278APending Publication Date: 2026-02-06ANHUI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511597829.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-11-04
Publication Date
2026-02-06

AI Technical Summary

Technical Problem

Existing nickel-based catalysts suffer from insufficient thermal stability, limited activity in the copolymerization of polar monomers, and difficulty in controlling the molecular weight of polymerization products during olefin homopolymerization or olefin/polar monomer copolymerization.

Method used

A neutral phosphonophenol nickel catalyst based on a tert-butyl structure was designed. By introducing tert-butyl groups at the para and meta positions of the metal center, and utilizing steric hindrance and electronic effects, a catalyst with high thermal stability and high catalytic activity was prepared for olefin homopolymerization or olefin/polar monomer copolymerization.

Benefits of technology

The thermal stability and catalytic activity of the catalyst were improved, and efficient copolymerization of polar monomers was achieved, resulting in polar polyolefins with functions such as adhesion and hydrophilicity, which broadened their application in high-end fields. In addition, the polymer has a narrow molecular weight distribution and excellent mechanical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121471278A_ABST
    Figure CN121471278A_ABST
Patent Text Reader

Abstract

The invention discloses a neutral phosphine phenol nickel catalyst based on a tert-butyl structure. The catalyst has a structure shown as a formula (I), wherein R1 and R2 are respectively and independently selected from hydrogen, C1-C20 alkyl, fluorine, chlorine, bromine, iodine, nitryl, hydroxyl, substituted silicon group and C1-C20 substituted alkyl; r3 is independently selected from C1-C20 alkyl, C1-C20 substituted alkyl, phenyl or substituted phenyl, R4 and R5 are independently selected from hydrogen, fluorine, chlorine, bromine, iodine, C1-C20 alkyl, aryl, an oxygen-containing group, a nitrogen-containing group, a sulfur-containing group, a boron-containing group, an aluminum-containing group, a phosphorus-containing group, a silicon-containing group or a tin-containing group; tert-butyl is introduced into para-position and meta-position of a ligand phenol oxygen ring, and a protection barrier is formed by utilizing the steric hindrance effect of the t-butyl, so that decomposition and deactivation of the catalyst under a high-temperature condition are inhibited, the catalyst can stably play a catalytic role in an industrial common medium-high-temperature polymerization environment, and the process adaptation range of the catalyst is widened.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of catalyst technology, and in particular to a neutral phosphonophenol nickel catalyst based on a tert-butyl structure, its preparation method, and its application as a catalyst for olefin homopolymerization or copolymerization of olefins with polar monomers. Background Technology

[0002] Polyolefins have rapidly gained a pivotal position in the global plastics industry due to their abundant raw material sources, low cost, excellent overall performance, and ease of processing. Their products are widely used in almost all sectors of the national economy, including packaging, agriculture, automotive, electronics, healthcare, and consumer goods.

[0003] Despite the massive annual production of polyolefin materials, one of their biggest drawbacks is their non-polar nature, a characteristic that severely limits their application in high-end fields. In practical industrial and daily life scenarios, non-polar polyolefins struggle to achieve good compatibility and bonding with polar materials such as polar polymers, inorganic fillers, and functional additives, resulting in inherent limitations in composite material preparation and functional modification. Introducing polar functional groups through chemical means can not only improve these performance shortcomings but also endow polyolefins with new functions such as adhesion, dyeability, and hydrophilicity, thereby broadening their application boundaries in high-end packaging, automotive lightweighting, and high-value-added electronic components.

[0004] The copolymerization of olefins with polar monomers is a key pathway to endow polyolefins with polarity, and the efficient execution of this process relies heavily on the development and application of high-performance catalysts. In recent decades, nickel-based catalysts have received widespread attention and been used in academia and industry to study the copolymerization of olefins and polar monomers due to their water stability and high tolerance to polar groups. In the late 1970s, SHOP catalysts demonstrated their unique advantages in olefin polymerization. Subsequently, researchers successfully synthesized corresponding monopolar phosphonophenol catalysts by precisely controlling the ortho- and para-substituents of phenoxy groups on a series of phenyl and naphthyl phosphonophenol ligands and rationally designing phosphorus substituents, significantly improving the activity and selectivity of the catalysts for olefin polymerization. Li Yuesheng's research group innovatively introduced large-volume substituents onto the ligands, effectively suppressing the β-H elimination reaction, thereby enabling the preparation of high-molecular-weight polyolefin materials. This type of phosphonophenol-nickel catalyst can efficiently catalyze the synthesis of high-molecular-weight functionalized polyolefins with highly polar monomer doping at relatively low monomer concentrations, providing a new technical pathway for the preparation of functionalized polyolefin materials. The research group of Chen Changle at the Chinese Academy of Sciences introduced cerium oxide groups into phosphonol nickel catalysts to prepare heterogeneous catalysts with specific structures, which significantly improved the activity of ethylene polymerization and provided a new technical solution for the application of heterogeneous catalytic systems in olefin polymerization.

[0005] The aforementioned research findings provide insights into how metal salt micro-sizing strategies can precisely and ingeniously optimize the polymerization performance of phosphonol nickel catalysts at the molecular level. While research on transition metal catalysts in olefin homopolymerization or olefin / polar monomer copolymerization is extensive, several challenges remain, such as insufficient catalyst thermal stability, limited activity in copolymerizing polar monomers, and difficulty in controlling the molecular weight of polymer products. This invention aims to address these technical pain points by developing a superior phosphonol nickel catalyst system. By adding tert-butyl groups at the para and meta positions of the metal center, and utilizing steric hindrance and electronic effects, a series of ligands and catalysts are designed and synthesized. These are then applied to olefin homopolymerization or olefin / polar monomer copolymerization to improve the catalyst's thermal stability, catalytic activity, and polymer molecular weight. This will promote the functionalization and high-performance development of polyolefin materials, meeting the increasingly diverse demands of high-end industries for polyolefin materials. Summary of the Invention

[0006] This application provides a neutral phosphonophenol nickel catalyst based on a tert-butyl structure. By adding tert-butyl groups at the para and meta positions of the metal center, ligands and catalysts are prepared using steric hindrance and electronic effects. The catalyst exhibits high thermal stability, catalytic activity, and polymer molecular weight when applied to olefin homopolymerization or olefin / polar monomer copolymerization.

[0007] This application provides a neutral phosphonophenol nickel catalyst based on a tert-butyl structure, the catalyst having the structure shown in formula (I): (I); R1 and R2 are independently selected from hydrogen, C1-C20 hydrocarbon groups, fluorine, chlorine, bromine, iodine, nitro, hydroxyl, substituted silicon groups, and C1-C20 substituted hydrocarbon groups, respectively; R3 is independently selected from C1-C20 hydrocarbon groups, C1-C20 substituted hydrocarbon groups, phenyl or substituted phenyl groups; R4 and R5 are independently selected from hydrogen, fluorine, chlorine, bromine, iodine, C1-C20 hydrocarbon groups, aryl, oxygen-containing groups, nitrogen-containing groups, sulfur-containing groups, boron-containing groups, aluminum-containing groups, phosphorus-containing groups, silicon-containing groups or tin-containing groups.

[0008] Furthermore, R1 and R2 can form bonds and rings with each other, and R4 and R5 can also form bonds and rings with each other.

[0009] Furthermore, R1 and R2 are independently selected from hydrogen.

[0010] This application provides a phosphonophenol ligand containing a tert-butyl group, the ligand having a structure as shown in formula (II): (II); R1 and R2 are independently selected from hydrogen, C1-C20 hydrocarbon groups, fluorine, chlorine, bromine, iodine, nitro, hydroxyl, substituted silicon groups, and C1-C20 substituted hydrocarbon groups, respectively. R1 and R2 can form bonds or rings with each other. R3 is independently selected from C1-C20 hydrocarbon groups, C1-C20 substituted hydrocarbon groups, phenyl or substituted phenyl groups, and C1-C20 alicyclic or aromatic hydrocarbon groups.

[0011] This application provides a method for preparing a catalyst-type (I) structure, the specific process of which is as follows: Under an argon or nitrogen atmosphere, the ligand of formula (II) and the nickel metal source are dissolved in a good solvent. Then, the ligand solution is slowly added dropwise to the nickel metal source solution through a constant pressure dropping funnel and stirred. After reacting at room temperature for 1-12 hours, the solution is filtered. The filtrate is dried under reduced pressure in a vacuum drying oven to remove the solvent and obtain the catalyst of formula (I). The general reaction formula is shown below: .

[0012] Furthermore, the nickel metal source can be any one of Py2NiMe2, Py2NiSiMe3, or NiCl(PPh3)2Ph.

[0013] Further good solvents can be toluene or tetrahydrofuran.

[0014] This application provides a method for preparing a ligand (II) structure, the specific process of which is as follows: By structure (a) The product structure was obtained after a protective reaction with MOMCl (chloromethyl methyl ether) under nitrogen or argon atmosphere. (a-1), after the product (a-1) reacts with butyllithium, the structure... (b) The MOMCl (chloromethyl methyl ether) protective structure of the ligand is prepared by adding it to the reaction system. Then, hydrochloric acid is added to remove the protecting group to obtain the ligand with ligand (II) structure.

[0015] This application provides a method for preparing polyolefins, the specific process of which is as follows: In a protective gas atmosphere, the catalyst shown in formula (I) is dissolved in a solvent; n-heptane is added to the reaction flask and heated to the desired temperature. After reaching the desired temperature, the catalyst solvent is injected into a reaction flask containing ethylene.

[0016] Furthermore, nitrogen can be used as the protective gas.

[0017] Furthermore, the solvent added to the catalyst shown in formula (I) can be an oil-based solvent, and the heating temperature is controlled at 80°C.

[0018] This application provides an example of the use of ligand (II) as a catalyst for homopolymerization of olefins or copolymerization of olefins with polar monomers.

[0019] Furthermore, the polar monomers include at least one of methyl acrylate, tert-butyl acrylate, methyl 10-undecenoate, and 10-undecenoic acid.

[0020] Furthermore, the molar ratio of the polar monomer to the catalyst shown in formula (I) is between 1:100 and 1:5000.

[0021] One or more technical solutions provided in the embodiments of this application have at least the following technical effects or advantages: 1. By introducing tert-butyl groups at the para and meta positions of the phenolic ring in the ligand, the steric hindrance effect of the tert-butyl groups forms a protective barrier, inhibiting the decomposition and deactivation of the catalyst under high temperature conditions. This allows the catalyst to stably exert its catalytic effect in the medium and high temperature polymerization environments commonly used in industry, broadening the process adaptability range of the catalyst and solving the problem that traditional nickel-based catalysts in the prior art have insufficient thermal stability and are difficult to adapt to high temperature polymerization processes in industry.

[0022] 2. By leveraging the electronic effect of tert-butyl groups to regulate the charge density of nickel centers, the catalyst's tolerance to different types of polar monomers, such as those containing ester groups, halogens, and hydroxyl groups, is enhanced. This enables efficient copolymerization of ethylene with polar monomers, providing an effective solution for preparing polar polyolefins with new functions such as adhesion and hydrophilicity, and facilitating the expansion of polyolefin materials' applications in high-end fields. Furthermore, the steric hindrance of tert-butyl groups can reduce chain transfer phenomena, resulting in more uniform polymer chain growth. This not only allows for effective control of polymer molecular weight but also enables the acquisition of polymerization products with narrow molecular weight distributions, improving the mechanical and processing properties of polyolefin materials and meeting the high-performance requirements of high-end industries for polyolefin materials. Attached Figure Description

[0023] Figure 1 The chemical formula for the tert-butyl structure neutral phosphonophenol nickel catalyst of this application is shown. Figure 2 The ligand of Example 1 of this application 1 H NMR spectrum; Figure 3 The ligand of Example 1 of this application 31 P NMR spectrum; Figure 4 The ligand of Example 1 of this application 13 C NMR spectrum; Figure 5 The ESI-MS spectrum of the ligand in Example 1 of this application is shown. Figure 6 The ligand of Example 2 of this application 1 H NMR spectrum; Figure 7 The ligand of Example 2 of this application 31 P NMR spectrum; Figure 8 The ligand of Example 2 of this application 13 C NMR spectrum; Figure 9 The ESI-MS spectrum of the ligand in Example 2 of this application is shown. Figure 10 The catalyst of Example 3 of this application 1 H NMR spectrum; Figure 11 The catalyst of Example 3 of this application 31 P NMR spectrum; Figure 12 The catalyst of Example 3 of this application 13 C NMR spectrum; Figure 13 The catalyst of Example 4 of this application 1 H NMR spectrum; Figure 14 The catalyst of Example 4 of this application 31 P NMR spectrum; Figure 15 The catalyst of Example 4 of this application 13 C10 NMR spectrum. Detailed Implementation

[0024] To facilitate understanding of the present invention, a more complete description will be given below with reference to the accompanying drawings. Preferred embodiments of the invention are shown in the drawings. However, the invention can be implemented in many different forms and is not limited to the embodiments described herein. Rather, these embodiments are provided to provide a thorough and complete understanding of the disclosure of the invention.

[0025] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used herein in the description of the invention is for the purpose of describing particular embodiments only and is not intended to be limiting of the invention. The term "and / or" as used herein includes any and all combinations of one or more of the associated listed items.

[0026] The following examples illustrate the specific content of the invention, providing data on ligand synthesis, metal compound synthesis, and ethylene polymerization or copolymerization methods. The synthesis of complexes and polymerization processes are carried out under anhydrous and oxygen-free conditions. All sensitive substances are stored in glove boxes, all solvents undergo rigorous drying and dehydration, and ethylene gas is purified using dehydration and deoxygenation columns. Unless otherwise specified, all raw materials can be purchased and used directly. The NMR spectrometer used was a Bruker 400MHz instrument; the elemental analysis was performed by the Physics and Chemistry Center of the University of Science and Technology of China; the molecular weight and molecular weight distribution were determined by high-temperature GPC; and the mass spectrometry was performed by a Thermo LTQ Orbitrap XL.

[0027] Example 1 The preparation process of the ligand-type II1 structure is as follows: Before weighing 100 mmol (equivalent to 20.6 g) of 2,4-di-tert-butylphenol, dry it in a vacuum drying oven at 80°C for 4 hours to remove adsorbed moisture. When adding the material, use the reduction method: place 100 mmol (equivalent to 20.6 g) of 2,4-di-tert-butylphenol into a 500 ml Schlenk flask, add 250 ml of tetrahydrofuran, and stir to form a uniform suspension. At this time, the suspension is white and translucent. The resulting suspension was cooled to 0°C, and 150 mmol of sodium hydride (equivalent to 6 g) was slowly added and mixed. The mixture was then heated to room temperature (approximately 25°C) and stirred for 1 hour. At this point, the suspension gradually turned into a pale yellow, clear solution, indicating that the phenolic hydroxyl groups of 2,4-di-tert-butylphenol had completely reacted with sodium hydride to form sodium phenolate. The mixture was then cooled to 0°C, and 150 mmol of MOMCl was slowly injected. The mixture was carefully heated to room temperature. After 3 hours, 20 mL of water was added to a Schlenk flask, and stirring was continued for 1 hour to terminate the reaction. At this point, the system separated into two layers: a pale yellow organic phase on top and a colorless aqueous phase on the bottom. The mixture was transferred to a 500 mL separatory funnel and the organic phase was separated under argon protection. The organic phase was concentrated under reduced pressure using a rotary evaporator and purified by silica gel column chromatography, using pure petroleum ether as eluent, to obtain a colorless, transparent liquid MOMCl protected product. 1 H NMR verification of the structure of MOMCl protected product (see reference) Figure 2 , Figure 2 The ligand of Example 1 of this application 1 The H NMR spectrum shows that the position of the characteristic peaks is consistent with the chemical environment of the MOMCl protected product, confirming the successful protection reaction. The MOMCl protected product was dissolved in 200 mL of tetrahydrofuran and placed at 0 °C. 11 mmol of n-BuLi (n-butyllithium) was added dropwise. After reacting for 2 h, 10 mmol of [a specific ingredient] was added. The mixture was slowly heated to room temperature and reacted for 12 hours. The reaction was quenched with water, and the organic phase was extracted with ether. The resulting organic phase was concentrated to 100 mL, deoxygenated by refrigeration, and 3 mL of concentrated hydrochloric acid was added under a nitrogen atmosphere. After reacting for 2 hours, NaHCO3 aqueous solution (sodium bicarbonate) was added for neutralization, followed by quenching with water. The organic phase was extracted with ether, and anhydrous Na2SO4 (sodium sulfate) was added for drying. After filtration and concentration, the white solid obtained by rapid column chromatography was complex II1. The reaction was analyzed by ESI-MS (…). Figure 5 The molecular ion peak was verified to be m / z=443.2.

[0028] The structural formula of ligand II1 obtained in the above embodiments is as follows: (II1).

[0029] Except ESI-MS ( Figure 5 In addition to verification, it also passes through 31 P NMR, 13 The structure of ligand II1 was further confirmed by C NMR: Figure 3 The ligand of Example 1 of this application 31 The single phosphorus signal peak in the P NMR spectrum proves that the phosphorus atom environment in the ligand is homogeneous. Figure 4 The ligand of Example 1 of this application 13 The C NMR spectrum shows that the number of carbon signal peaks and chemical shifts are completely matched with the carbon species and chemical environment in the structural formula (II1) of ligand II1. Figure 5 The ESI-MS spectrum of the ligand in Example 1 of this application shows that the molecular ion peak m / z=443.2 is consistent with the theoretical molecular weight of ligand II1, thus confirming the successful synthesis of ligand II1.

[0030] Example 2 The preparation process of the ligand-type II2 structure is as follows: Before weighing 100 mmol (equivalent to 20.6 g) of 2,4-di-tert-butylphenol, dry it in a vacuum drying oven at 80°C for 4 hours to remove adsorbed moisture. When adding the material, use the reduction method: place 100 mmol (equivalent to 20.6 g) of 2,4-di-tert-butylphenol into a 500 ml Schlenk flask, add 250 ml of tetrahydrofuran, and stir to form a uniform suspension. At this time, the suspension is white and translucent. The resulting suspension was cooled to 0°C, and 150 mmol of sodium hydride (equivalent to 6 g) was slowly added and mixed. The mixture was then heated to room temperature (approximately 25°C) and stirred for 1 hour. At this point, the suspension gradually turned into a pale yellow, clear solution, indicating that the phenolic hydroxyl groups of 2,4-di-tert-butylphenol had completely reacted with sodium hydride to form sodium phenolate. The mixture was then cooled to 0°C, and 150 mmol of MOMCl was slowly injected. The mixture was carefully heated to room temperature. After 3 hours, 20 mL of water was added to a Schlenk flask, and stirring was continued for 1 hour to terminate the reaction. At this point, the system separated into two layers: a pale yellow organic phase on top and a colorless aqueous phase on the bottom. The mixture was transferred to a 500 mL separatory funnel and the organic phase was separated under argon protection. The organic phase was concentrated under reduced pressure using a rotary evaporator and purified by silica gel column chromatography, using pure petroleum ether as eluent, to obtain a colorless, transparent liquid MOMCl protected product. 1 H NMR confirmed the structure of the MOMCl protected product (see [reference]). Figure 6 , Figure 6 The ligand of Example 2 of this application 1 The characteristic peak of methyl ether (-OCH2O-) (approximately 4.6-5.0 ppm) is clearly visible in the 1H NMR spectrum, proving that the MOMCl protecting group was successfully introduced; The MOMCl-protected product was dissolved in 200 mL of tetrahydrofuran and separated by silica gel column chromatography using pure petroleum ether as the eluent to obtain the product protected by MOMCl. This product was then dissolved in 200 mL of tetrahydrofuran, placed at 0 °C, and 11 mmol of n-BuLi (n-butyllithium) was added dropwise. After reacting for 2 h, 10 mmol of [unspecified ingredient] was added. The mixture was slowly heated to room temperature and reacted for 12 hours. The reaction was quenched with water, and the organic phase was extracted with diethyl ether. The resulting organic phase was concentrated to 100 mL, and deoxygenated by refrigeration. 3 mL of concentrated hydrochloric acid was added under a nitrogen atmosphere, and the reaction was carried out for 2 hours. NaHCO3 aqueous solution (sodium bicarbonate) was added for neutralization, and the reaction was quenched with water. The organic phase was extracted with diethyl ether, and anhydrous Na2SO4 (sodium sulfate) was added for drying. After filtration and concentration, the white solid obtained by rapid column chromatography was the complex II2.

[0031] The structural formula of ligand II2 obtained in the above embodiments is as follows: (II2).

[0032] pass 31 P NMR, 13 The structure of ligand II2 was fully characterized by C1 NMR and ESI-MS: Figure 7 The ligand of Example 2 of this application 31 The P NMR spectrum shows that the chemical shift of the phosphorus signal peak is consistent with the bonding environment of the phosphorus atom in ligand II2. Figure 8 The ligand of Example 2 of this application 13 The C NMR spectrum shows that the signal peak positions of characteristic carbons (such as tert-butyl carbon and aromatic ring carbon) are consistent with the theoretical values ​​of structural formula (II2). Figure 9 The ESI-MS spectrum of the ligand in Example 2 of this application shows that the molecular ion peak matches the theoretical molecular weight of ligand II2, confirming that the synthesis of ligand II2 was correct.

[0033] Example 3 The preparation process of the catalyst I1 structure is as follows: Weigh 1 mmol of ligand (II1). The solvent used was 50 mL of anhydrous toluene, and a 1.1 mmol nickel source was used with a molar ratio of 1:1.1 to ensure complete coordination of the ligands. In a nitrogen-atmospheric glove box, 1 mmol of ligand (II1) was added. The ligand solution was obtained by dissolving 1.1 mmol of nickel source in toluene. The ligand solution was then slowly added dropwise to the nickel source solution through a constant pressure dropping funnel and stirred. The reaction was carried out at room temperature for 4 h. The solution was filtered to obtain a brownish-yellow solution. The filtrate was dried under reduced pressure in a vacuum drying oven (vacuum degree 0.098 MPa, temperature 40 °C) for 4 h to obtain brownish-yellow solid catalyst I1.

[0034] The catalyst structure of the ligand I1 structure obtained in the above embodiments is as follows: (I1).

[0035] pass 1 H NMR, 31 P NMR, 13 The structure of catalyst I1 was characterized by C NMR to confirm the successful coordination reaction between ligand II1 and the nickel source: Figure 10 The catalyst of Example 3 of this application 1 H NMR spectrum, compared to ligand II1 1 H NMR spectrum ( Figure 2 The chemical shifts of the aromatic ring hydrogen and tert-butyl hydrogen are significantly shifted, proving that nickel ions form coordinate bonds with the phenolic oxygen group and phosphorus atom of the ligand; Figure 11 The catalyst of Example 3 of this application 31 The P NMR spectrum shows a phosphorus signal peak compared to ligand II1. 1 p NMR spectrum ( Figure 3 The shift to a lower or higher field (adjusted according to the actual spectral trend) further proves that phosphorus atoms participate in coordination. Figure 12 The catalyst of Example 3 of this application 13The C NMR spectrum showed that the change in the carbon signal peak was consistent with the change in the coordination environment of carbon in the structural formula (I1) of catalyst I1, and the brownish-yellow solid was finally confirmed as the target catalyst I1.

[0036] Py2NiMe2 can be used as the nickel source.

[0037] Example 4 The preparation process of the catalyst I2 structure is as follows: Weigh out 1 mmol of ligand (II2). The solvent used was 50 mL of anhydrous toluene, and a 1.1 mmol nickel source was used with a molar ratio of 1:1.1 to ensure complete coordination of the ligands. In a nitrogen-atmospheric glove box, 1 mmol of ligand (II2) was added. The ligand solution was obtained by dissolving 1.1 mmol of nickel source in toluene. The ligand solution was then slowly added dropwise to the nickel source solution through a constant pressure dropping funnel and stirred. The reaction was carried out at room temperature for 4 h. The solution was filtered to obtain a brownish-yellow solution. The filtrate was dried under reduced pressure in a vacuum drying oven (vacuum degree 0.098 MPa, temperature 40 °C) for 4 h to obtain a brownish-yellow solid catalyst I2.

[0038] The catalyst structure of the ligand I2 structure obtained in the above embodiments is as follows: (I2).

[0039] pass 1 H NMR, 31 P NMR, 13 The structure of the catalyst I2 was characterized by C NMR: Figure 13 The catalyst of Example 4 of this application 1 The 1H NMR spectrum shows that the chemical shift of the aromatic ring hydrogen in ligand II2 changes due to coordination with nickel ions, and there is no hydrogen signal peak of the free ligand, proving that the coordination reaction is complete. Figure 14 The catalyst of Example 4 of this application 31 The P NMR spectrum shows a single and shifted phosphorus signal peak, indicating that phosphorus atoms form a stable coordination with nickel ions and that there are no free phosphorus impurities in the catalyst. Figure 15 The catalyst of Example 4 of this application 13 The C NMR spectrum showed that the number and chemical shift of carbon signal peaks were completely matched with the theoretical structure of catalyst I2, confirming the successful preparation of I2.

[0040] Py2NiMe2 can be used as the nickel source.

[0041] Example 5 The preparation process of the catalyst I3 structure is as follows: Weigh out 1 mmol of ligand (II1). The solution used was a 1.5 mmol nickel source in a molar ratio of 1:1.5 to ensure complete coordination of the ligands. Anhydrous toluene (50 mL) was used as the solvent. In a nitrogen-atmospheric glove box, 1 mmol of ligand (II1) was added. The ligand solution was obtained by dissolving 1.5 mmol of nickel source in toluene. The ligand solution was then slowly added dropwise to the nickel source solution through a constant pressure dropping funnel and stirred. The reaction was carried out at room temperature for 6 h. The solution was filtered to obtain a brownish-yellow solution. The filtrate was dried under reduced pressure in a vacuum drying oven (vacuum degree 0.098 MPa, temperature 40 °C) for 4 h to obtain a brownish-yellow solid catalyst I3.

[0042] The catalyst structure of the ligand I3 obtained in the above embodiments is as follows: (I3).

[0043] Py2NiSiMe3 can be used as the nickel source.

[0044] Example 6 The preparation process of the catalyst I4 structure is as follows: Weigh out 1 mmol of ligand (II2). The solvent used was 1.5 mmol of anhydrous toluene in a molar ratio of 1:1.5 to ensure complete coordination of the ligands. In a nitrogen-atmospheric glove box, 1 mmol of ligand (II2) was added. The ligand solution was obtained by dissolving 1.5 mmol of nickel source in toluene. The ligand solution was then slowly added dropwise to the nickel source solution through a constant pressure dropping funnel and stirred. The reaction was carried out at room temperature for 6 h. The solution was filtered to obtain a brownish-yellow solution. The filtrate was dried under reduced pressure in a vacuum drying oven (vacuum degree 0.098 MPa, temperature 40 °C) for 4 h to obtain a brownish-yellow solid catalyst I4.

[0045] The catalyst structure of the ligand I4 obtained in the above embodiments is as follows: (I4).

[0046] Py2NiSiMe3 can be used as the nickel source.

[0047] Example 7 The preparation process of catalyst I5 structure is as follows: Weigh out 1 mmol of ligand (II1). The solution used was a 1.5 mmol nickel source in a molar ratio of 1:1.5 to ensure complete coordination of the ligands. The solvent used was 50 mL of tetrahydrofuran. In a nitrogen atmosphere, 1 mmol of ligand (II1) was added. The ligand solution was obtained by dissolving 1.5 mmol of metallic nickel in tetrahydrofuran. The ligand solution was then slowly added dropwise to the metallic nickel source solution through a constant pressure dropping funnel and stirred. The reaction was carried out at room temperature for 6 h. The solution was filtered to obtain a brownish-yellow solution. The filtrate was dried under reduced pressure in a vacuum drying oven (vacuum degree 0.098 MPa, temperature 40 °C) for 4 h to obtain a brownish-yellow solid catalyst I5.

[0048] The catalyst structure of the ligand I5 obtained in the above embodiments is as follows: (I5).

[0049] The nickel source can be NiCl(PPh3)2Ph.

[0050] Example 8 The preparation process of the catalyst I6 structure is as follows: Weigh out 1 mmol of ligand (II2). The solution used was a 1.5 mmol nickel source in a molar ratio of 1:1.5 to ensure complete coordination of the ligands. The solvent used was 50 mL of tetrahydrofuran. In a nitrogen atmosphere, 1 mmol of ligand (II2) was added. The ligand solution was obtained by dissolving 1.5 mmol of metallic nickel source in tetrahydrofuran. The ligand solution was then slowly added dropwise to the metallic nickel source solution through a constant pressure dropping funnel and stirred. The reaction was carried out at room temperature for 6 h. The solution was filtered to obtain a brownish-yellow solution. The filtrate was dried under reduced pressure in a vacuum drying oven (vacuum degree 0.098 MPa, temperature 40 °C) for 4 h to obtain brownish-yellow solid catalyst I6.

[0051] The catalyst with ligand I6 structure obtained in the above embodiments has the following structural formula: (I6).

[0052] The nickel source can be NiCl(PPh3)2Ph.

[0053] Referring to the characterization methods in Examples 3 and 4, by 1 H NMR, 31 P NMR, 13 C NMR for catalyst I x The structure was verified, and the spectral characteristics (such as the shift of the hydrogen / phosphorus / signal peaks after coordination, and the absence of free ligand impurity peaks) were consistent with those of the target catalyst I. x The structural formula is consistent, confirming the successful synthesis of the catalyst (for specific characterization data, please refer to the corresponding figures in Examples 3 and 4. Due to differences in catalyst structure, the spectral details are slightly different, and Examples 5 to 8 will not be shown separately).

[0054] Application Example 1 The catalysts prepared in Examples 3-8 were used to carry out ethylene polymerization reactions, and the specific polymerization methods are as follows: Before using the autoclave, rinse the inner wall with toluene twice, and purge with nitrogen (99.999% purity) five times. After the last purging, maintain the nitrogen pressure inside the autoclave at 0.1 atmospheres. Turn on the oil bath heating, set the temperature to 80℃, and hold for 10 minutes to ensure that the temperature inside the autoclave is stable at 80±0.5℃. In a glove box under nitrogen atmosphere, add 18 mL of n-heptane to a 350 mL autoclave equipped with a magnetic stirrer, an oil bath heating device, and a thermometer. Connect the container to the high-pressure pipeline and evacuate the pipeline. Heat the container to 80°C in the oil bath and keep it at that temperature for 10 minutes. 2 mL of toluene containing 2 μmol of nickel phosphonophenol catalyst was injected into the polymerization system of the reaction mixture using a syringe. The valve was closed, the ethylene pressure was adjusted to 8 atmospheres, and the reaction was allowed to proceed for 30 min. After the reaction was completed, the ethylene in the reactor was slowly vented, the reactor lid was opened, and ethanol (analytical grade) was added to precipitate the polymer. The mixture was stirred for 10 minutes to form a white flocculent precipitate. The solid was collected by filtration under reduced pressure using a funnel and washed with ethanol to remove residual solvent and catalyst. The solid was then placed in a vacuum drying oven (80℃, 0.095MPa) and dried for 8 hours until a constant weight was obtained to obtain a white polyethylene solid.

[0055] The results of ethylene polymerization catalyzed by the catalysts prepared in Examples 3-8 are shown in Table 1:

[0056] Table 1 Table 1 shows the polymerization reaction conditions: catalyst 2 μmol, n-heptane 18 mL, ethylene 8 atm, reaction time 30 min, polymerization temperature 80℃; b activity 10 6 g•mol -1 •h -1 c. Melting point was determined using a differential scanning calorimeter; d. Number-average molecular weight 10 4 gmol -1 The molecular weight was determined by GPC using polystyrene as the standard and trichlorobenzene as the solvent at 150°C.

[0057] As shown in Table 1, the polyethylene yield of catalyst I1 in Example 3 was 0.8 g (Table 1), and the number-average molecular weight was 15.1 × 10⁻⁶ as determined by GPC. 4 The molecular weight distribution of g / mol and molecular weight distribution of 2.5 indicate that the polymer chain growth is uniform. The melting point determined by DSC is 140.4℃, which is higher than that of conventional polyethylene (about 135℃). This is because the steric hindrance of the catalyst inhibits chain branching, resulting in a polymer with higher crystallinity (crystallinity calculated by DSC is 65%).

[0058] Application Example 2 The catalysts prepared in Examples 3 and 4 were used to carry out the copolymerization reaction of ethylene with polar monomers. The specific polymerization methods are as follows: In a glove box and under a nitrogen atmosphere, add 20 mL of toluene to a 350 mL autoclave (equipped with a magnetic stirrer, an oil bath heater, and a thermometer), and add any one of the following polar monomers: tert-butyl acrylate, methyl 10-undecenoate, or 6-chloro-1-hexene, to adjust the concentration of the polar monomers to different levels. Then connect the container to the high-pressure line and evacuate the line, and set the container temperature to 80°C and keep it at that temperature for 5 minutes. The catalysts prepared in Examples 3 and 4 were then dissolved in 2 mL of toluene using 10 μmol of catalyst and injected into the autoclave using a syringe. The ethylene valve was opened, ethylene was introduced into the autoclave, and the ethylene pressure was adjusted to 8 atmospheres. The reaction was carried out for 30 min. After the reaction was stopped, the autoclave was opened, ethanol was added to precipitate the solid, the mixture was filtered under reduced pressure, and dried in a vacuum drying oven to obtain a white solid.

[0059] The results of the polymerization of ethylene with polar monomers catalyzed by the catalysts prepared in Examples 3 and 4 are shown in Table 2:

[0060] Table 2 The polymerization conditions in Table 2 are as follows: Ni 5 μmol, ethylene 0.8 MPa, tert-butyl acrylate 0.1 mol / L, methyl 10-undecenoate 1.0 mol / L, 6-chloro-1-hexene 1.0 mol / L, polymerization temperature 80℃, n-heptane 20 mL, reaction time 30 minutes; b. activity unit 10 5 g(molcat.×h). c The melting point of the copolymer is d, the mole fraction of polar monomer units in the copolymer is e, and the number-average molecular weight is 10. 4 g / mol.

[0061] Table 2 shows that the catalysts described above can catalyze the preparation of polyethylene modified with polar functional groups. Table 2 also shows that the catalyst in this application can catalyze the copolymerization of ethylene with polar monomers to prepare polar polyolefins under certain conditions, with a maximum activity reaching 4.44 × 10⁻⁶. 5 gmol -1 h -1 Melting point: 112.7–123.6℃; Number average molecular weight: 22.9 × 10⁻⁶ 4 g / mol; Product analysis: In Example 3, the yield of the copolymerization of catalyst I1 with 6-chloro-1-hexene was 1.11 g (Table 2), with an activity of 4.44 × 10⁻⁶.5 The g / (molcat.×h) was the highest in this group; the number-average molecular weight determined by GPC was 20.0×10⁻⁶. 4 The g / mol and molecular weight distribution of 1.6 indicate that there are few chain transfer reactions in the copolymerization reaction and that the catalyst has good tolerance to polar monomers (no catalyst deactivation). Differential results: Methyl 10-undecenoate exhibits weaker coordination between the ester group and the metal center, resulting in lower copolymerization activity (4.24 × 10⁻⁶). 5 The g / (molcat.×h) ratio is slightly lower than that of 6-chloro-1-hexene; tert-butyl acrylate has greater steric hindrance and the lowest insertion ratio (1.3-1.7%), but the product has the narrowest molecular weight distribution (1.4-2.0), which is due to the steric hindrance effect inhibiting the chain exchange reaction.

[0062] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. For those skilled in the art, the present invention can have various modifications and variations. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A neutral phosphonophenol nickel catalyst based on a tert-butyl structure, characterized in that: The catalyst has a structure as shown in formula (I): (I); R1 and R2 are independently selected from hydrogen, C1-C20 hydrocarbon groups, fluorine, chlorine, bromine, iodine, nitro, hydroxyl, substituted silicon groups, and C1-C20 substituted hydrocarbon groups, respectively; R3 is independently selected from C1-C20 hydrocarbon groups, C1-C20 substituted hydrocarbon groups, phenyl or substituted phenyl groups; R4 and R5 are independently selected from hydrogen, fluorine, chlorine, bromine, iodine, C1-C20 hydrocarbon groups, aryl, oxygen-containing groups, nitrogen-containing groups, sulfur-containing groups, boron-containing groups, aluminum-containing groups, phosphorus-containing groups, silicon-containing groups or tin-containing groups.

2. The neutral phosphonophenol nickel catalyst based on a tert-butyl structure as described in claim 1, characterized in that: R1 and R2 can form a ring with each other, and R4 and R5 can also form a ring with each other.

3. The neutral phosphonophenol nickel catalyst based on a tert-butyl structure as described in claim 1, characterized in that: R1 and R2 are independently selected from hydrogen.

4. The neutral phosphonophenol nickel catalyst based on a tert-butyl structure as described in claim 1, characterized in that: Phosphophenolic ligands containing tert-butyl groups are also provided, the ligands having the structure shown in formula (II): (II); R1 and R2 are independently selected from hydrogen, C1-C20 hydrocarbon groups, fluorine, chlorine, bromine, iodine, nitro, hydroxyl, substituted silicon groups, and C1-C20 substituted hydrocarbon groups, respectively. R1 and R2 can form bonds or rings with each other. R3 is independently selected from C1-C20 hydrocarbon groups, C1-C20 substituted hydrocarbon groups, phenyl or substituted phenyl groups, and C1-C20 alicyclic or aromatic hydrocarbon groups.

5. Any one of the neutral phosphonophenol nickel catalysts based on a tert-butyl structure as described in claims 1-4, characterized in that: A method for preparing the ligand (II) structure is provided, the specific process of which is described below. By structure (a) The product structure obtained after protection reaction with MOMCl under nitrogen or argon atmosphere. (a-1), after the product (a-1) reacts with butyllithium, the structure... (b) The MOMCl protective structure of the ligand is prepared by adding it to the reaction system, and then hydrochloric acid is added to remove the protecting group to obtain the ligand with ligand (II) structure.

6. A method for preparing a neutral phosphonophenol nickel catalyst based on a tert-butyl structure, characterized in that: Includes the following processes, Under an argon or nitrogen atmosphere, the ligand of formula (II) and the nickel metal source are dissolved in a good solvent. Then, the ligand solution is slowly added dropwise to the nickel metal source solution through a constant pressure dropping funnel and stirred. After reacting at room temperature for 1-12 hours, the solution is filtered. The filtrate is dried under reduced pressure in a vacuum drying oven to remove the solvent and obtain the catalyst of formula (I). The general reaction formula is shown below: 。 7. The method for preparing a neutral phosphonophenol nickel catalyst based on a tert-butyl structure as described in claim 6, characterized in that: The nickel source can be any one of Py2NiMe2, Py2NiSiMe3, or NiCl(PPh3)2Ph.

8. A method for preparing polyolefins, characterized in that: The specific process is as follows. In a protective nitrogen atmosphere, the catalyst shown in formula (I) is dissolved in a solvent; n-heptane is added to the reaction flask and heated to the desired temperature. After the catalyst solvent is reached, it is injected into a reaction flask containing ethylene.

9. A method for preparing polyolefins as described in claim 8, characterized in that: The solvent added to the catalyst shown in formula (I) can be an oily solvent, and the heating temperature is controlled at 80℃.

10. The application of a neutral phosphonophenol nickel catalyst with a tert-butyl structure in a copolymerization catalyst with a polar monomer, characterized in that: The polar monomers include at least one of methyl acrylate, tert-butyl acrylate, methyl 10-undecenoate, and 10-undecenoic acid; The molar ratio of the polar monomer to the catalyst shown in formula (I) is between 1:100 and 1:5000.